Postharvest fumigation with nitric oxide at the pre-climacteric and climacteric-rise stages influences ripening and quality in mango fruit - Zaharah, Sakimin; Singh, Zora (Headly Brothers, 2011)
Mango fruit ripen extremely quickly, which limits their distribution to distant markets. Mature mango (Mangifera indica ‘Kensington Pride’) fruit harvested at the pre-climacteric (PC) and climacteric rise (CR) stages of ripening were fumigated with different concentrations (0, 5, 10, 20, or 40 μl l–1) of nitric oxide (NO) to investigate the effects of this free-radical gas on fruit ripening and quality. Fumigation with NO at 20 μl l–1 or 40 μl l–1 was more effective at delaying and/or suppressing the climacteric rise in ethylene production and reducing the rate of respiration when applied to fruit at the PC stage than to fruit at the CR stage. NO-fumigation retarded the development of fruit colour, with lower chromicity L, a, b, and C values and higher h° values compared to untreated control fruit. Higher concentrations of NO (i.e., 20 μl l–1 or 40 μl l–1) were more effective at retarding fruit softening during ripening. The pulp of ripe, NO-fumigated fruit exhibited improved rheological properties (i.e., cohesiveness, springiness, and chewiness) and increased shikimic acid contents, but reduced concentrations of total sugars and fructose compared to non-fumigated, ripe fruit. In conclusion, NO-fumigation at 20 μl l–1 or 40 μl l–1 was more effective when applied early, at the PC stage, than later during the CR stage.